Anatomical study of perigastric fascial space and guidance for laparoscopic approach - Jin, Guoliang; Duan, Shuquan; Guan, Ana; Wang, Zhepeng; Zhang, Ranhao; Qiao, Wenjuan; Wang, Qiuhong; Zheng, Liansheng (Frontiers in Surgery, 2024)
ObjectiveTo study the anatomic characteristics of gastric peritoneum fascia space and provide a safe surgical approach for laparoscopic radical gastrectomy.MethodThe morphological characteristics of perigastric fascia and fascial space and the course of important blood vessels were observed and studied in 2 fresh adult cadavers, 5 formalin immersed cadavers and 56 patients undergoing total gastrectomy. The hemoglobin, albumin, prealbumin, total protein, operation time, intraoperative blood loss, number of lymph node dissection and the incidence of complications before and after laparoscopic total gastrectomy with different approaches were statistically analyzed.ResultsThrough dissecting the cadaver, it is found that the space of the posterior gastric fascia space is suitable for laparotomy and laparoscopic surgery. The space between the prepancreatic fascia and the posterior gastric fascia is located in a plane, and the posterior gastric fascial space is connected with the gastrosplenic space and hepatogastric space. Through three different plane approaches, all can enter the space without blood vessels and nerves, so as to achieve complete gastrectomy. Statistical analysis of patients undergoing total gastrectomy with different approaches showed that there was no significant difference in operation time, intraoperative blood loss, number of lymph node dissection and postoperative complications among the three approaches (P > 0.05). There was no significant difference in postoperative hemoglobin, albumin, prealbumin and total protein (P > 0.05).ConclusionsThe space of the posterior gastric fascia space is suitable for laparotomy and laparoscopic surgery.the application of the anatomical study of perigastric fascial space in laparoscopic radical resection of gastric cancer not only accords with the tumor-free principle of radical resection of tumor, improves the safety of operation, but also reduces the occurrence of complications such as bleeding and important organ injury.